VD_FINDINFO HC / 2011 / 598 vom 13. Oktober 2011 - VD Tribunal cantonal (2011)
MESURE PROVISIONNELLE, DIVORCE, OBLIGATION D'ENTRETIEN | 176 al. 1 ch. 1 CC, 649 al. 1 CC, 649 al. 2 CC, 276 al. 1 CPC (CH)